Peer Conformity in Terms of Gender - Muthia Febio Anjori; Daharnis Daharnis (Jurnal Neo Konseling, 2023)
Peer conformity is one of the causes of problems that many students do at school. This study aims to describe peer conformity and differences in peer conformity in terms of gender. This research uses a quantitative method with a comparative descriptive research type. The population in this study were 631 students in grades X, XI, and XII SMA Adabiah Padang for the academic year 2022/2023 and a sample of 259 students was drawn using proportional random sampling. Collecting data in this study using a peer conformity questionnaire. Data were processed using descriptive analysis and t-test with the help of SPSS version 20. The results showed that peer conformity behavior at Adabiah Padang High School was in the "medium" category. There is a significant difference between students' peer conformity in terms of gender. Percentage of conformity among male students (57.9%) and female students (64.6%) with a significance value (2-tailed) of 0.000. The results of this study have implications for Guidance and Counseling service activities.